Analysis of Lapan Security Access Based on Firewall Log in Center Eight - Subakti, Adityo Jaya (Institute of Computer Science (IOCS), 2024)
Analysis of Network Security Access Space Agency Based Firewall Log In LAPAN Center. Supervisor LIPUR SUGIYANTA, Ph.D and Drs. BACHREN ZAINI, M.Pd. Increased Denial Of Service attacks, and other types of computer network interference, making security an important issue to be considered by all those who take advantage of the presence of the virtual world today. LAPAN Center system along with the information contained within is no exception contained attacks on access computer network security. Such attacks can be prevented at an early stage by analyzing at each access that will go on network security in LAPAN. This research at Analysis of Network Access to know and learn access of network security in firewall log LAPAN Center. This research was conducted with several stages of observation and interviews to employees of LAPAN Center infrastructure. After the stage of observation and interviews, the researchers conducted further data collection and analysis of firewall logs. The study states that the analysis of security access network based firewall log in LAPAN Center in the form of six messages that occur when a network will pass through the firewall. It can be concluded that by doing some analysis phases of network security access based firewall log in LAPAN Center produces a record of every incident inside the firewall logs. The study states that the analysis of security access network based firewall log in LAPAN Center in the form of six messages that occur when a network will pass through the firewall. It can be concluded that by doing some analysis phases of network security access based firewall log in LAPAN Center produces a record of every incident inside the firewall logs. The study states that the analysis of security access network based firewall log in LAPAN Center in the form of six messages that occur when a network will pass through the firewall. It can be concluded that by doing some analysis phases of network security access based firewall log in LAPAN Center produces a record of every incident inside the firewall logs.